Media Belajar Interaktif Bahasa Inggris untuk Siswa di Rumah Belajar KSB - Diasti, Krismalita Sekar; Hartono, Heny (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
English subject becomes elective course given by elementary schools. Indeed, schools are given authority to regulate the implementation of English language learning yet many elementary schools still provide English language learning to students. The primary reason is that to prepare young generations in facing working competition globally which one of the digital world demands’ is mastering English. English language learning for elementary school students will be more captivating if teachers use learning media. This community service focused on developing interactive learning media using ADDIE method. The result of this product implementation showed that students were more motivated to learn English. Elementary school teachers are hoped to be more creative in English language teaching process in order to motivate and engage students to learn English.